Mapping and Future Potential of Cocoa Commodity Base Regions in Indonesia - Adyanti, Amanda Sekar; Aji, Joni Murti Mulyo; Hani, Evita Soliha (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2025)
Cocoa is a prominent global export with strong competitiveness in the international market. During the 2019-2022 period, there was positive growth in cocoa exports while domestic cocoa production declined. The variability of cocoa production across provinces is due to the different levels of cocoa development in each region. This study aims to map cocoa base and non base regions in Indonesia and examine the characteristics of cocoa distribution across the provinces of Indonesia. This study is important because there have been limited studies about regional mapping of cocoa at the national level. It is also important to know the condition of regional mapping in the future. The regions observed in this study include 33 provinces in Indonesia that produce cocoa. The study uses secondary data which includes variables related to cocoa production and production of superior plantation commodities for seven years (2017-2023). The analysis used to answer the primary objective is Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analysis, while the secondary objective uses Localisation and Specialisation analysis. The findings reveal 10 provinces as cocoa base regions, with Southeast Sulawesi exhibiting the highest LQ. North Sulawesi province has been identified as potential areas for future development. While 18 provinces have shifted from base regions to non base regions or are not prospective in the future. Localisation and Specialisation indices below 1 indicate that cocoa cultivation is geographically dispersed, with no single region dominating production.